A Fuzzy Machine Learning Based Approach for Promoting Sustainability in Agriculture. - Mohapatra, Smaranika; Chaudhary, Neha (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Agriculture being the backbone of India, various factors affect the sustainability of the food products and he farmers. Factors like soil, geographic region, and climatic parameters impact significantly on crop yield and productivity. The farmers in India follow the traditional approach for harvesting. This is due to the lack of awareness and not having adequate knowledge of the challenges the parameters have on crop products due to which it often leads to financial and social loss to the farmers. An approach is much required to provide an efficient solution to extend help and sustainability of the farmers. The current study recommends a fuzzy logic-based recommendation system for the cash crops to help the farmers have financial and social sustainability. The proposed recommendation system is designed using a Fuzzy Inference System (FIS) using the rule-based logic approach to achieve an accuracy of 93% which is examined and validated.